THE EFFECT OF PROFITABILITY, FIRM SIZE, AND OWNERSHIP STRUCTURE ON DIVIDEND POLICY - Ni Putu Ayu Indah Wulandari; Made Reina Candradewi (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
A dividend policy represents a company's strategy for distributing earned profits to its shareholders either via dividends or by reinvesting them back into the company. Such policies are crucial for attracting investors in the financial markets. The aim of this research is to examine how profitability, size of the company, ownership by managers, and ownership by institutions effect dividend policy. The research is centered on firms operating within the property and real estate industries on the Indonesia Stock Exchange, spanning the period from 2019 to 2023. It involves a selection of seven firms using a purposive sampling approach. The collection of data was derived from the annual financial statements of these firms. For the data analysis, the study employed techniques of multiple linear regression analysis, facilitated by the use of IBM SPSS 26 software. Findings from this investigation show that profitability and managerial ownership significantly impact dividend policy, whereas the size of the company and institutional ownership do not show a significant effect on dividend policy.